Study of Inorganic Waterproof Agent on the Performance of Desulfurization Gypsum Products - Ding, Yi; Ren, Qifang; Hu, Puhua (Asian Journal of Chemistry, 2013)
Gypsum block is based on building gypsum as main raw material, by adding water mixing, casting molding and drying into light construction gypsum products. This experiment mainly studied plant desulfurization gypsum in adding inorganic waterproof agent on block setting time, apparent density, compressive strength, flexural strength and coefficient softening, finding a good water resistant agent and experimental formula. When the 25 % inorganic waterproof agent was added, the product apparent density is 1087 kg/m3, compressive strength is 11.53 Mpa, flexural strength is 3.40 Mpa, soften coefficient is 0.63.